2017
DOI: 10.1002/app.45678
|View full text |Cite
|
Sign up to set email alerts
|

Self‐aggregated nanoparticles of N‐dodecyl,N′‐glycidyl(chitosan) as pH‐responsive drug delivery systems for quercetin

Abstract: In this study, pH‐responsive amphiphilic chitosan (CS) nanoparticles were used to encapsulate quercetin (QCT) for sustained release in cancer therapy. The novel CS derivatives were obtained by synthesis with 2,3‐epoxy‐1‐propanol, also known as glycidol, followed by acylation with dodecyl aldehyde. Characterization was performed by spectroscopic, viscosimetric, and size‐determination methods. Critical aggregation concentration, morphology, entrapment efficiency, drug release profile, cytotoxicity, and hemocompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…This product was grafted on collagen or nisin to obtain the sorbent materials suitable for pharmaceutic and medical applications [ 35 , 36 ]. Similar hydroxyalkylation with glycidol was also reported [ 37 ]. Generally, the chitosan hydroxyalkylated with epoxides can be further substituted with carboxyl groups [ 38 , 39 ].…”
Section: Introductionsupporting
confidence: 85%
“…This product was grafted on collagen or nisin to obtain the sorbent materials suitable for pharmaceutic and medical applications [ 35 , 36 ]. Similar hydroxyalkylation with glycidol was also reported [ 37 ]. Generally, the chitosan hydroxyalkylated with epoxides can be further substituted with carboxyl groups [ 38 , 39 ].…”
Section: Introductionsupporting
confidence: 85%
“…The results further revealed that the incubation time of the cells with QCT is directly related to the reduction of cell viability, which suggests that a higher incubation time would have led to higher toxicity. In addition, recent studies have confirmed the bioavailability and effectiveness of QCT against MCF-7 cells [7,51,52].…”
Section: Mtt Assaymentioning
confidence: 85%
“…Pedro et al synthesized N -dodecyl- N ′-glycidyl(chitosan) for the delivery of quercetin [ 189 ]. The hydrodynamic parameters of quercetin loaded hydrophobically modified CS micelles were measured by dynamic light scattering showing sizes from 140 to 260 nm and Zeta-potential values from +18.7 to +30.4 mV at pH 7.4.…”
Section: Hydrophobic Modification Of Chitosan and Derivatives For mentioning
confidence: 99%